Profiling of Somatic Mutations in Phaeochromocytoma and Paraganglioma by Targeted Next Generation Sequencing Analysis. (25th March 2015) - Luchetti, Andrea; Walsh, Diana; Rodger, Fay; Clark, Graeme; Martin, Tom; Irving, Richard; Sanna, Mario; Yao, Masahiro; Robledo, Mercedes; Neumann, Hartmut P. H.; Woodward, Emma R.; Latif, Farida; et al.
Abstract : At least 12 genes ( FH, HIF2A, MAX, NF1, RET, SDHA, SDHB, SDHC, SDHD, SDHAF2, TMEM127, and VHL ) have been implicated in inherited predisposition to phaeochromocytoma (PCC), paraganglioma (PGL), or head and neck paraganglioma (HNPGL) and a germline mutation may be detected in more than 30% of cases. Knowledge of somatic mutations contributing to PCC/PGL/HNPGL pathogenesis has received less attention though mutations in HRAS, HIF2A, NF1, RET, and VHL have been reported. To further elucidate the role of somatic mutation in PCC/PGL/HNPGL tumourigenesis, we employed a next generation sequencing strategy to analyse "mutation hotspots" in 50 human cancer genes. Mutations were identified for HRAS (c.37G>C; p.G13R and c.182A>G; p.Q61R) in 7.1% (6/85); for BRAF (c.1799T>A; p.V600E) in 1.2% (1/85) of tumours; and for TP53 (c.1010G>A; p.R337H) in 2.35% (2/85) of cases. Twenty-one tumours harboured mutations in inherited PCC/PGL/HNPGL genes and no HRAS, BRAF, or TP53 mutations occurred in this group. Combining our data with previous reports of HRAS mutations in PCC/PGL we find that the mean frequency of HRAS/BRAF mutations in sporadic PCC/PGL is 8.9% (24/269) and in PCC/PGL with an inherited gene mutation 0% (0/148) suggesting that HRAS/BRAF mutations and inherited PCC/PGL genes mutations might be mutually exclusive. We report the first evidence for BRAF mutations in the pathogenesis of PCC/PGL/HNPGL.